Association of a four‐gene model with allergic diseases: Two‐year follow‐up of a birth cohort study - Li Hua; Fen Yang; Qian Chen; Quanhua Liu; Ruoxu Ji; Haipei Liu; Jianmin Ye; Jun Zhang; Jianhua Zhang; Yixiao Bao (Immunity, Inflammation and Disease)
Abstract Background Our previous study has developed a four‐gene model involving IL13 rs20541, IL4 rs2243250, ADRB2 rs1042713, and FCER1B rs569108 associated with asthma and atopy in Chinese Han children. However, whether the gene model is associated with allergies in early life has yet to be determined. This study aimed to apply the gene model in a birth cohort to investigate its associations with the development of allergic diseases in Chinese Han toddlers. Methods Five hundred and ninety‐seven children from a birth cohort completing 2‐year follow‐up were included. Epidemiologic information and cord blood were collected. Children were genotyped for the above polymorphisms and divided into high or low genetic risk groups based on the genotypes. Subjects were followed at 6, 12, and 24 months, with information on allergic diseases collected via standard questionnaires and assessed by specialists. Results Two hundred and eighty‐four children were divided into a high‐risk group and 313 into a low‐risk group. Between the two groups, a significant difference was only found in delivery mode among all the subject characteristics (p = .025). After stratification for delivery mode, children at high risk were more likely to develop eczema (relative risk [RR] = 1.46, p = .040) over 2 years of follow‐up compared with those at low risk. No significant associations were found between genetic risk and food allergy, wheezing and allergic rhinitis (p > .05). Conclusion The gene model was significantly associated with the development of eczema in Chinese Han toddlers. Long‐term follow‐up along with functional and replication studies on the gene model are still needed in future.